Aristolochia guillermoi (Aristolochiaceae), a new species from Peru and a key to identify the Aristolochia taxa with branched trichomes - González, Favio; Esquerre-Ibañez, Boris (Phytotaxa, 2025)
A new species, Aristolochia guillermoi is described from seasonal dry forests of northern Peru, in the Department of Piura, at elevations between 1000 and 1600 m. The new species is similar to A. andina from central and southern Bolivia. They differ in several characters of the leaves, the perianth, the capsule and the seeds. Aristolochia guillermoi is the fourth Aristolochia species known to have branched trichomes, a very unusual epidermal trait in the genus, which also occurs in A. andina, A. fosteri and A. killipiana. Notably, all these species are restricted to the Andes of Ecuador, Peru and Bolivia, at elevations between 1000 and 2580 m. A key and a map of distribution for these species are provided.